2009
DOI: 10.1111/j.1475-4991.2009.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Industrial and Aggregate Measures of Productivity Growth in China, 1982–2000

Abstract: We estimate productivity growth for 33 industries covering the entire Chinese economy using a time series of input-output tables covering 1982-2000. Capital input is measured using detailed investment data by asset and labor input uses demographic information from household surveys. We find a wide range of productivity performance at the industry level. We then show how these industry growth accounts may be consistently aggregated to deliver a decomposition of aggregate GDP growth. For the 1982-2000 period agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 20 publications
0
25
1
Order By: Relevance
“…This is a result that is much smaller than all previous productivity studies on the Chinese economy based on the aggregate approach-for example, about 40 per cent contribution estimated by Bosworth and Collins (2008) and by Perkins and Rawski (2008). Our finding is, however, also small when compared with the only work in the literature applying the same approach but specifically to the period 1982-2000 (Cao et al 2009). The finding herein is in fact about one-third of their result of 2.51 per cent per annum.…”
Section: Resultscontrasting
confidence: 82%
See 1 more Smart Citation
“…This is a result that is much smaller than all previous productivity studies on the Chinese economy based on the aggregate approach-for example, about 40 per cent contribution estimated by Bosworth and Collins (2008) and by Perkins and Rawski (2008). Our finding is, however, also small when compared with the only work in the literature applying the same approach but specifically to the period 1982-2000 (Cao et al 2009). The finding herein is in fact about one-third of their result of 2.51 per cent per annum.…”
Section: Resultscontrasting
confidence: 82%
“…It has since been used in Jorgenson et al (2005aJorgenson et al ( , 2005b to quantify the role of information technology (IT)-producing and IT-using industries in the US economy. The approach is now the international standard and has also been applied to the Chinese economy in Cao et al (2009) In this equation, Y is output, K is an index of capital service flows, L is an index of labour service flows and M is an index of intermediate inputs purchased from domestic industries and/or imported. Note that all input variables are indexed by time but this is suppressed for notational convenience.…”
Section: Accounting For Industry Origin Of Tfpmentioning
confidence: 99%
“…The measuring methods included the Solow residual method, C-D production function, translog production function, stochastic frontier analysis (SFA), data envelopment analysis (DEA), etc. For example, Cao et al [11] estimated productivity growth for 33 Chinese industries covering 1982-2000. The study showed that the main source of output growth was capital accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…(), Cao et al . (), Nilsen et al . (), and work based on the European Union (EU) KLEMS database such as that of O'Mahony and Timmer () and Timmer et al .…”
Section: Introductionmentioning
confidence: 99%